Gestión De Riesgos Mayores En El Centro De Capacitación, Transferencia Tecnológica, Producción y Servicios (CETTEPS) De La Universidad Nacional De Chimborazo - Yumisaca Carguacundo, Alex Mauricio (2022)
ABSTRACT: This project was carried out at the Center for Training, Technology Transfer, Production and Services (CETTEPS) to manage the site's significant risks identified internally and externally. They were evaluated, and it was proposed control actions in an Emergency Plan concatenated to the regulations requested by the Risk Management Department of Riobamba Gadm for their respective approval. The population is 25, including workers, teachers, and students. Information was collected using on-site inspection, risk checklist, INSST matrix, observing each of the spaces, resources, and threats inherent to the site, and determining the risks of fire, seismic, and ash fall to identify the risks. These were subsequently evaluated using methodologies associated with each risk detected, such as NFPA, MESERI, MEIPEE, FEMA154 SEISMIC VULNERABILITY INDEX, VULNERABILITY MATRIXES, HAZARD MAPS, DOCUMENTATION HISTORY OF HAZARDOUS EVENTS. These provided a qualitative and quantitative assessment concerning their standard values to determine the risk level of CETTEPS. With the values obtained from the methodologies applied, preventive and corrective actions could be oriented, thus proposing structural measures, non-structural measures, action protocols, formation of a multifunctional brigade, and actions before, during, and after an emergency. The Emergency Plan was elaborated and presented to the Risk Management Department of Riobamba Gadm, obtaining the review and approval through a certificate of compliance, which has a term of 45 days for its legalization by the authorities of the UNACH. This project helps reduce the impact of the detected risks. It also prepares people who use the facilities to act in an emergency and protect their physical integrity. Keywords: Majors Risks, Emergency Plan, Natural and anthropic hazards